Keynes – the ethical inspired economist - Olesen, Finn (Brazilian Keynesian Review, 2024)
To some, the discipline of economics should not escape the fact that it is, at least to some extent, based on ethical and moral aspects. Historically, it was in general accepted that economics had to include ethical considerations. However, later it became fashionable to focus primarily on doing positive economics. Deductive logic combined with a formal mathematical reasoning became the way to do macroeconomics in more modern times. As such, the old Keynesian paradigm founded on the writings of Keynes, the ethical inspired economist, became overthrown by economists inspired by Friedman, one of the foremost proponents of positive economics. However, can macroeconomists really do without concerning themselves with questions of morality? Ought macroeconomics not to have an ethical foundation? The present article aims at discussing some selected aspects of both the need for economics to have some form of ethical anchorage and the ethical kind of understanding that Keynes advocated.